G-C3N4 / TiO2 photocatalyst and preparation method thereof
By mixing fly ash, titanium dioxide and urea, g-C3N4/TiO2 photocatalysts loaded on fly ash are prepared, which solves the problems of high preparation cost and poor settlementability of C3N4/TiO2 photocatalysts in the prior art, and achieves the effect of reducing preparation cost and improving photocatalytic efficiency.
Patent Information
- Application Number
- CN202411706908.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-04
AI Technical Summary
The existing C3N4/TiO2 photocatalysts have high preparation costs and poor settlement properties in the suspension system, making them difficult to recover.
By mixing fly ash, titanium dioxide and urea, drying and calculating, a g-C3N4/TiO2 photocatalyst was prepared and supported on fly ash to reduce the preparation cost.
It reduces the preparation cost of supported catalysts, solves the problem of fly ash polluting the environment, and improves photocatalytic efficiency, simple process flow, strong operability, and easy to promote industrially.
Smart Images

Figure BDA0005154714540000051 
Figure BDA0005154714540000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a g-C3N4 / TiO2 photocatalyst and a preparation method thereof. Background Art
[0002] C3N4 / TiO2 has the advantages of a wide light response range and stable chemical properties, and is one of the most widely studied photocatalysts. However, C3N4 / TiO2 has poor sedimentation properties, is difficult to recover in a suspension system, and is prone to agglomeration in the presence of high-valent cations. When treating gases, it is also prone to excessive loss under conditions of high air intake rates, which is not conducive to reuse. Loading C3N4 / TiO2 on a carrier solves the above problems to a certain extent. For example, Wang and Liu loaded C3N4 / TiO2 on ZSM-5 mesoporous materials and waste zeolites, respectively, and achieved good results. However, these loaded carriers require complex preparation processes, which increases the preparation cost of loaded photocatalysts.
[0003] Fly ash is one of the largest industrial solid wastes in my country. According to statistics, 0.25-0.30 tons of fly ash are usually produced for every ton of coal burned. The large amount of fly ash accumulation will inevitably cause serious environmental problems. If fly ash is used as a carrier for photocatalyst, it can not only solve the problem of serious environmental pollution caused by fly ash, but also reduce the preparation cost of supported catalysts. Summary of the invention
[0004] The main purpose of the present invention is to provide a g-C3N4 / TiO2 photocatalyst and a preparation method thereof, so as to solve the problem of high preparation cost of C3N4 / TiO2 catalyst in the prior art.
[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a g-C3N4 / TiO2 photocatalyst is provided, and the preparation method comprises: step S1, mixing raw materials including fly ash, titanium dioxide and urea to obtain a mixture; step S2, drying and roasting the mixture in sequence to obtain a g-C3N4 / TiO2 photocatalyst.
[0006] Furthermore, in the above step S1, the mass ratio of fly ash, titanium dioxide and urea is 1:1-5:2-9.
[0007] Furthermore, in the above step S1, the density of fly ash is 1.010-1.030 g / cm 3 , and / or the bulk density of fly ash is 0.050~0.065g / cm 3 , and / or the average particle size of fly ash is 29 to 32 μm, and / or the specific surface area of fly ash is 14 to 17 m 2 / g, and / or the water content of fly ash is 2-3%.
[0008] Furthermore, in the above step S1, the raw material also includes a solvent, and the preferred solvent is water and / or anhydrous ethanol.
[0009] Furthermore, in the above step S1, the volume ratio of the solvent to the total mass of the raw materials is 10 to 20 mL / g.
[0010] Furthermore, in the above step S1, the mixing method is wet grinding, the wet grinding temperature is 25-30°C, and / or the wet grinding time is 4-8h; preferably, a planetary ball mill is used for wet grinding, and / or the type of grinding balls used in wet grinding is zirconia balls, and / or the diameter of the grinding balls is 3-5mm, and / or the volume ratio of the balls is 1:1-1:3.
[0011] Furthermore, in the above step S2, the drying temperature is 80-120° C., and / or the drying time is 12-24 hours.
[0012] Furthermore, in the above step S2, the calcination temperature is 400-650°C, and / or the calcination time is 2-6 hours, and / or the heating rate during the calcination process is 1-5°C / min.
[0013] According to another aspect of the present invention, a g-C3N4 / TiO2 photocatalyst is provided. The g-C3N4 / TiO2 photocatalyst is prepared by the aforementioned preparation method.
[0014] Furthermore, the specific surface area of the g-C3N4 / TiO2 photocatalyst is 45 to 65 m 2 / g, and / or the average particle size of g-C3N4 / TiO2 photocatalyst is 3 to 10 μm.
[0015] The technical solution of the present invention is applied. Fly ash is a solid waste generated after coal combustion. Fly ash particles are usually porous honeycomb-like and have a large specific surface area, which makes fly ash have good adsorption performance. By loading g-C3N4 / TiO2 on the surface or pores of fly ash, the preparation cost of the supported catalyst can be reduced, and the problem of serious environmental pollution caused by fly ash can be solved. At the same time, fly ash interacts with TiO2 and urea, which is conducive to the separation of electron-hole pairs, thereby improving the photocatalytic efficiency. The process of the present invention is simple, highly operable, short in time, has low requirements on equipment, and is easy to promote industrialization. DETAILED DESCRIPTION
[0016] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0017] As analyzed in the background technology of this application, there is a problem of high preparation cost of C3N4 / TiO2 catalyst in the prior art. In order to solve the above problem, this application provides a g-C3N4 / TiO2 photocatalyst and a preparation method thereof.
[0018] In a typical embodiment of the present application, a method for preparing a g-C3N4 / TiO2 photocatalyst is provided, and the preparation method comprises: step S1, mixing raw materials including fly ash, titanium dioxide and urea to obtain a mixture; step S2, drying and calcining the mixture in sequence to obtain a g-C3N4 / TiO2 photocatalyst.
[0019] Fly ash is a solid waste produced after coal combustion. Fly ash particles are usually porous honeycomb structures with a large specific surface area, which makes fly ash have good adsorption properties. By loading g-C3N4 / TiO2 on the surface or pores of fly ash, the preparation cost of supported catalysts can be reduced, and the problem of serious environmental pollution caused by fly ash can be solved. At the same time, fly ash interacts with TiO2 and urea, which is conducive to the separation of electron-hole pairs, thereby improving the photocatalytic efficiency. The process of the present invention is simple, highly operable, short in time, has low requirements on equipment, and is easy to promote industrialization.
[0020] In one embodiment of the present application, in the above step S1, the mass ratio of fly ash, titanium dioxide and urea is 1:1-5:2-9.
[0021] The preferred mass ratio of fly ash, titanium dioxide and urea is within the above range, which is more conducive to the smooth formation of g-C3N4 and helps to control the loading of g-C3N4 and TiO2 on fly ash in a more appropriate mass ratio, thereby helping to improve the photocatalytic performance of g-C3N4 / TiO2 photocatalyst.
[0022] In one embodiment of the present application, in the above step S1, the density of fly ash is 1.010-1.030 g / cm 3 , and / or the bulk density of fly ash is 0.050~0.065g / cm 3 , and / or the average particle size of fly ash is 29 to 32 μm, and / or the specific surface area of fly ash is 14 to 17 m 2 / g, and / or the water content of fly ash is 2-3%.
[0023] It is preferred to control the density, bulk density and specific surface area of fly ash within the above ranges, which helps to control the porosity and particle size of the fly ash, thereby helping to improve the loadability of g-C3N4 / TiO2 on fly ash.
[0024] In one embodiment of the present application, in the above step S1, the raw material also includes a solvent, and the preferred solvent is water and / or anhydrous ethanol.
[0025] In the present application, water is used as a solvent to help evenly disperse fly ash, titanium dioxide and urea in the water, thereby improving the uniformity and contact area of each raw material in the mixture.
[0026] In one embodiment of the present application, in the above step S1, the volume ratio of the solvent to the total mass of the raw materials is 10 to 20 mL / g.
[0027] The above preferred conditions are helpful to improve the dispersion uniformity of fly ash in the solvent, thereby helping to improve the efficiency and effect of drying and roasting.
[0028] In one embodiment of the present application, in the above step S1, the mixing method is wet grinding, the wet grinding temperature is 25-30°C, and / or the wet grinding time is 4-8h; preferably, a planetary ball mill is used for wet grinding, and / or the type of grinding balls used in wet grinding is zirconia balls, and / or the diameter of the grinding balls is 3-5mm, and / or the material-ball ratio is 1:1-1:3.
[0029] The above preferred conditions are helpful to improve the uniformity of the mixture and control the particle size of the mixture, thus laying a foundation for controlling the particle size of the g-C3N4 / TiO2 photocatalyst. At the same time, wet grinding can also effectively reduce the particle size of the material, increase the specific surface area of the material, reduce energy consumption, and reduce pollution to the environment.
[0030] In order to fully remove the moisture in the mixture and minimize the effect of moisture on the roasting process, in one embodiment of the present application, in the above step S2, the drying temperature is preferably 80 to 120° C., and / or the drying time is 12 to 24 hours.
[0031] In one embodiment of the present application, in the above step S2, the calcination temperature is 400-650°C, and / or the calcination time is 2-6h, and / or the heating rate during the calcination process is 1-5°C / min.
[0032] The above preferred calcination conditions help to improve the efficiency and effect of calcination, while promoting the formation of g-C3N4 / TiO2 photocatalyst, and help to increase the specific surface area of g-C3N4 / TiO2 photocatalyst, thereby improving the catalytic performance of g-C3N4 / TiO2 photocatalyst.
[0033] In another typical embodiment of the present application, a g-C3N4 / TiO2 photocatalyst is provided, and the g-C3N4 / TiO2 photocatalyst is prepared by the aforementioned preparation method.
[0034] The g-C3N4 / TiO2 photocatalyst prepared by the above preparation method not only benefits from the larger specific surface area of pulverized coal, thus having excellent catalytic performance, but also greatly reduces the cost.
[0035] In one embodiment of the present application, the specific surface area of the TiO2 photocatalyst is 45 to 65 m 2 / g, and / or the average particle size of g-C3N4 / TiO2 photocatalyst is 3 to 10 μm.
[0036] The g-C3N4 / TiO2 photocatalyst with the above preferred specific surface area and average particle size is more conducive to use as a photocatalyst and has excellent photocatalytic performance.
[0037] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0038] The fly ash raw material of the following examples is fly ash from the power plant of the State Energy Group Corporation, and its chemical composition is shown in Table 1.
[0039] Table 1 Chemical composition of fly ash from power plant of China Energy Group Co., Ltd. (wt%)
[0040] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> other 34.51 46.80 2.49 2.37 0.18 0.65 1.48 11.52
[0041] Example 1
[0042] 1g of fly ash (density of fly ash is 1.010g / cm 3 , bulk density is 0.540g / cm 3 The average particle size is 29.32 μm and the specific surface area is 14.93 m 2 / g, water content is 2%), 2g titanium dioxide, 4g urea are mixed, put into a ball mill, 100mL deionized water is added, and wet milling is performed at room temperature using a planetary ball mill, the grinding balls are zirconium oxide balls (diameter is 3mm), the material ball volume ratio is 1:1, and a mixture is obtained after wet milling for 6h;
[0043] The mixture was dried in an oven at 100°C for 12 h, and then the dried product was transferred to a crucible and placed in a muffle furnace for calcination at 550°C with a heating rate of 2°C / min. The temperature was maintained for 4 h to obtain a g-C3N4 / TiO2 photocatalyst.
[0044] Example 2
[0045] The difference from Example 1 is that 1 g of fly ash, 2 g of titanium dioxide and 9 g of urea are mixed to obtain a mixture, and finally the g-C3N4 / TiO2 photocatalyst is obtained.
[0046] Example 3
[0047] The difference from Example 1 is that 1 g of fly ash, 5 g of titanium dioxide and 9 g of urea are mixed to obtain a mixture, and finally the g-C3N4 / TiO2 photocatalyst is obtained.
[0048] Example 4
[0049] The difference from Example 1 is that 1 g of fly ash, 0.8 g of titanium dioxide and 1.6 g of urea are mixed to obtain a mixture, and finally the g-C3N4 / TiO2 photocatalyst is obtained.
[0050] Example 5
[0051] The difference from Example 1 is that the density of fly ash is 1.020 g / cm 3 , bulk density is 0.060g / cm 3 The average particle size is 30.34 μm and the specific surface area is 14.75 m 2 / g, the water content is 2%, and finally g-C3N4 / TiO2 photocatalyst is obtained.
[0052] Example 6
[0053] The difference from Example 1 is that the mass of fly ash is 1 g, the volume ratio of the solvent to the total mass of the raw materials is 8 mL / g, and finally g-C3N4 / TiO2 photocatalyst is obtained.
[0054] Example 7
[0055] The difference from Example 1 is that the volume ratio of the balls in the wet grinding is 1:2, and the g-C3N4 / TiO2 photocatalyst is finally obtained.
[0056] Example 8
[0057] The difference from Example 1 is that the calcination temperature is 400°C, and g-C3N4 / TiO2 photocatalyst is finally obtained.
[0058] Example 9
[0059] The difference from Example 1 is that the calcination temperature is 650°C, and g-C3N4 / TiO2 photocatalyst is finally obtained.
[0060] Example 10
[0061] The difference from Example 1 is that the calcination temperature is 700°C, and g-C3N4 / TiO2 photocatalyst is finally obtained.
[0062] Embodiment 11
[0063] The difference from Example 1 is that the calcination temperature is 380°C, and g-C3N4 / TiO2 photocatalyst is finally obtained.
[0064] Comparative Example 1
[0065] 2g of TiO2, 4g of urea and 100g of deionized water were mixed, ultrasonically treated for 30min, stirred for 4h, and then dried for 12h. After drying, the solid was transferred to a muffle furnace and calcined at 400℃ with a heating rate of 2℃ / min and a holding time of 5h. The sintered sample was cooled to room temperature to finally obtain g-C3N4 / TiO2.
[0066] Take 100 mL of methyl orange solution with a concentration of 20 mg / L and a pH of 6, add 0.50 g of g-C3N4 / TiO2 photocatalyst prepared in the embodiment and the comparative example, oscillate at a constant temperature for 1 hour, turn on the visible light source for 150 minutes after the adsorption reaches equilibrium, and conduct a photocatalytic degradation experiment. After the experiment, take out the solution, filter it, and measure the concentration of methyl orange in the supernatant with an ultraviolet spectrophotometer. According to R=C0-C e / C0, calculate the removal rate, where R is the removal rate (%), C0 is the initial concentration of methyl orange in the solution (mg / L), C e is the concentration of methyl orange in the solution after the photocatalytic reaction (mg / L). The experimental results are shown in Table 2.
[0067] Table 2
[0068]
[0069]
[0070] Among them, the increased calcination temperature in Example 10 has little effect on the methyl orange removal efficiency of the obtained g-C3N4 / TiO2 photocatalyst, but its energy consumption is slightly higher.
[0071] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0072] Fly ash is a solid waste produced after coal combustion. Fly ash particles are usually porous honeycomb structures with a large specific surface area, which makes fly ash have good adsorption properties. By loading g-C3N4 / TiO2 on the surface or pores of fly ash, the preparation cost of supported catalysts can be reduced, and the problem of serious environmental pollution caused by fly ash can be solved. At the same time, fly ash interacts with TiO2 and urea, which is conducive to the separation of electron-hole pairs, thereby improving the photocatalytic efficiency. The process of the present invention is simple, highly operable, short in time, has low requirements on equipment, and is easy to promote industrialization.
[0073] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a g-C3N4 / TiO2 photocatalyst, characterized in that: The preparation method comprises: Step S1, mixing raw materials including fly ash, titanium dioxide and urea to obtain a mixture; Step S2, drying and calcining the mixture in sequence to obtain a g-C3N4 / TiO2 photocatalyst.
2. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of the fly ash, the titanium dioxide and the urea is 1:1-5:2-9.
3. The preparation method according to claim 1 or 2, characterized in that: In step S1, the density of the fly ash is 1.010-1.030 g / cm 3 , and / or the bulk density of the fly ash is 0.050 to 0.065 g / cm 3 , and / or the average particle size of the fly ash is 29 to 32 μm, and / or the specific surface area of the fly ash is 14 to 17 m 2 / g, and / or the water content of the fly ash is 2-3%.
4. The preparation method according to any one of claims 1 to 3, characterized in that In the step S1, the raw material further comprises a solvent, and preferably the solvent is water and / or anhydrous ethanol.
5. The preparation method according to claim 4, characterized in that: In the step S1, the volume ratio of the solvent to the total mass of the raw materials is 10 to 20 mL / g.
6. The preparation method according to any one of claims 1 to 5, characterized in that In the step S1, the mixing method is wet grinding, the wet grinding temperature is 25 to 30° C., and / or the wet grinding time is 4 to 8 hours; Preferably, a planetary ball mill is used for the wet grinding, and / or the grinding balls used in the wet grinding are zirconium oxide balls, and / or the diameter of the grinding balls is 3 to 5 mm, and / or the volume ratio of the balls is 1:1 to 1:
3.
7. The preparation method according to any one of claims 1 to 6, characterized in that In the step S2, the drying temperature is 80-120°C, and / or the drying time is 12-24 hours.
8. The preparation method according to any one of claims 1 to 7, characterized in that In the step S2, the calcination temperature is 400-650°C, and / or the calcination time is 2-6 hours, and / or the heating rate during the calcination process is 1-5°C / min.
9. A g-C3N4 / TiO2 photocatalyst, characterized in that: The g-C3N4 / TiO2 photocatalyst is prepared by the preparation method described in any one of claims 1 to 8.
10. The g-C3N4 / TiO2 photocatalyst according to claim 9, characterized in that: The specific surface area of the g-C3N4 / TiO2 photocatalyst is 45 to 65 m 2 / g, and / or the average particle size of the g-C3N4 / TiO2 photocatalyst is 3 to 10 μm.